Interactive Multimedia Development of Indonesian Endemic Plants: Species Uniqueness with MDLC Approach - Yani Ami Atun; Bryan Bagus Pambudi; Bayu Azra Maulana (Jurnal Indonesia Sosial Teknologi, 2024)
This research explores the development of interactive multimedia with a focus on Indonesia's endemic plants, applying the Multimedia Development Lifecycle (MDLC) as a design approach. MDLC provides a systematic foundation with six related phases, including concept, design, material collection, assembly, testing, and distribution, to ensure the success of educational media development. The hardware and software required for multimedia creation are also outlined, providing a comprehensive overview of the technology infrastructure used. Design steps include concepts that consider visual uniqueness, intuitive navigation, deep content, and connectivity to learning needs. The storyboard design breaks down into sections, including splash screens, main menus, material menus, evaluations, and information, each designed to provide an optimal user experience. Material collection involves selecting multimedia assets, including images, letters, and icons, integrated using Adobe Illustrator software. The assembly process is carried out through Construct 2, creating an interactive and dynamic interface. Black Box testing is conducted to verify compliance with optimal design and functionality. Supporting theories, such as multimedia concepts, MDLC, and the definition of Indonesia's endemic flora, provide a strong theoretical foundation. Results and discussions include evaluations of Alpha and Beta testing that show positive user responses. Overall, this research concludes that interactive multimedia successfully provides an effective and engaging learning experience, ready for widespread distribution.